PROPHYLACTIC ADMINISTRATION OF DEXAMETHASONE VERSUS MEPERIDINE FOR PREVENTION OF POST-SPINAL SHIVERING AMONG PARTURIENTS UNDERGOING CESAREAN SECTION - Devi Sharma (Regmi), Bharati; Regmi, Subi; Prasad Deo, Gopendra; Dhital, Ashok (Journal of Chitwan Medical College, 2024)
Background: Perioperative shivering is defined as an involuntary, oscillatory muscular activity lasting for longer than 15 seconds. Studies have shown that its prevalence of 50%-80% in neuraxial anesthesia causing. It leads to increased metabolic activity, oxygen consumption, intracranial, and intraocular pressure, cardiac output, peripheral resistance, carbon dioxide production, and lactic acidosis and causes unpleasant experiences to the patients. Methods: This is a hospital based, prospective, comparative study conducted at Chitwan Medical College from June 2023 to Feb 2024 among parturients between 18-35 years, undergoing caesarean section (C/S), under spinal anaesthesia aimed to compare the effectiveness of prophylactic administration of meperidine, dexamethasone in prevention of perioperative shivering. Total 158 patients of ASA physical status II were included and with alternate randomization, were allocated into two groups with 79 participants in each. Patients who were allocated in group D received 4mg of IV Dexamethasone and those allocated in group M received 25mg of IV Meperidine after delivery of baby. Results: The overall incidence of post spinal shivering in our study was 14.6% of which, 11.4% belonged to Group M and 3.2% belonged to Group D (p < 0.05). The intensity of shivering was significantly less in Group D as compared to Group M (p < 0.001) at T1, T6, T7 and T8 point of observation. Conclusions: It was concluded that Dexamethasone is superior to Meperidine in alleviating post-spinal shivering in parturients undergoing elective cesarean section under subarachnoid block with additional benefits of less occurrence of sedation, nausea and vomiting.